Selected aspects of parenting by mothers of children aged 1-3 years in Medical Officer of Health area Kaduwela - Wickramasinghe, E.P (My University, 2010)
The aim of this study was to assess the level of provision of emotional care and discipline control by the mothers having children aged 1 to 3 years visiting the well baby clinics of Medical Officer of Health area Kaduwela and to find out socio-demographic and other factors of the mothers related to parenting. This nd to be having statistically significant association with the level of provision of emotional care by the mothers in this study. Results did not have any statistically significant associations between level of provision of emotional care and factors like maternal level of education, state of employment, family income and current health status of the mother. But these factors had remarkable differences in the level of emotional care. Gaps in ways of provision of emotional care and discipline control were identified and it is recommended to emphasize on these measures in the existing maternal and childcare programme in this country in order to uplift the quality of the parenting practices by the mothers.